Compressive Properties of Tropical Natural Fibers Reinforced Epoxy Polymer Composites - Jauhar Fajrin (Jurnal Ilmu dan Teknologi Kayu Tropis, 2016)
Fiber reinforced plastics composites are particularly valued for their high tensile strength. Other mechanical properties, especially compressive strength is often overlooked during the characterization process. In fact, the comparatively low compression strength of some composite reduces their promising application. This paper presents the experimental investigation on the compressive strength of epoxy polymer composites reinforced by natural fibers of sisal, jute, hemp and bamboo grown in tropical area. The natural fiber composites were prepared using vacuum bagging method and the fibers were treated with alkali treatment prior to further processing. The results showed that the average values of compressive strength obtained in this work ranged from 31.69 MPa to 86.64 MPa. Those results indicate that the obtained compressive strength of natural fibers composites investigated in this research were comparable to the results of previous work, which ranged from from 16.75 MPa to 108.07 MPa.